Development of non-destructive methods of the characterization of mesenchymal stem cell differentiation in vitro - Surrati, Amal (2018)
Real time monitoring of stem cells has been a growing area of interest over the past decade because of new regenerative medicine approaches. Also, the effect of culture composition on stem cell metabolic pathways and their regulation of cellular fate are of increasing importance. In our project, non-destructive metabolomic analysis of stem cells and their physiological status during proliferation and differentiation stages will be investigated. This will be achieved through mass spectrometric analysis of released metabolites by LCMS and GC/MS; therefore stem cells should ideally be cultured in a specialized format to maintain their physiological properties during non-invasive live analysis while being compatible with real time GC/MS. To address this issue, mesenchymal stem cell attachment, proliferation and differentiation were tested in 20ml glass vials required for GC/MS analysis. Environmental conditions in which MSCs can proliferate under sealed condition and at room temperature were also optimized. Our data show the potential of MSCs to attach, proliferate and differentiate in 20ml glass vessels. Furthermore, cells could maintain their metabolic activity for approximately 6hrs not only under hypoxic but also hypothermic conditions. Therefore, live time analysis of their chemical volatiles could be performed in a format compatible for LC-MS and GC/MS which will be performed for undifferentiated MSCs and their differentiated populations (osteogenic and adipogenic lineages) in the next phase of the project. A specific treatment approach has emerged from hMSCs osteogenic study and identified a particular pathway suggested to be involved in chondrogenesis, and linked to the collagen II biosynthesis. The treatment is based on on natural products (L-lysine and ascorbic acid) and when tested on human cell cultures, was observed to significantly increase the morphological and functional markers of chondrogenesis, suggesting its potential to promote de novo cartilage formation in vitro.